Implementation of The Learning Sciences Approach Through The Reading and Thinking Aloud Method to Improve Reading Comprehension Skills of Elementary School Students - Erna Sefriani Sabuna; Henny Dewi Koeswanti; Stefanus Christian Relmasira (Postgraduate, University of Mataram, 2025)
This study examines the implementation of the Learning Sciences approach through the Reading and Thinking Aloud method to improve the reading comprehension skills of elementary school students who have difficulty in understanding the meaning of text content. Qualitative research with a case study approach was conducted at SD Negeri Salatiga 06, Salatiga City, Central Java Province, with 26 Grade 6 learners as the research subjects. Data were collected through participatory observation, semi-structured interviews, and Y-charts, and analyzed using MAXQDA application. The analysis revealed three main clusters: Material Content Cluster, which shows that presenting material through visual media, interactive discussions, and a dynamic classroom environment increases understanding and learning satisfaction; the Constructivism Theory Cluster, which emphasizes the importance of social interaction, scaffolding, and collaboration between teachers and learners in developing critical thinking skills, in line with Vygotsky's Zone of Proximal Development concept; and the Content Use of Technology Cluster, which highlights the role of technological innovations, such as the use of QR codes, in creating interactive learning experiences and increasing learning motivation. The research findings show that the implementation of the Reading and Thinking Aloud method supported by technology significantly improves learners' reading comprehension and encourages active engagement and collaboration in the classroom. The data suggests that this learning strategy shows the potential of the Solution to address the problem of weak reading comprehension skills at the primary school level